Phytochrome type B family: The abiotic stress responses signaller in plants - Junior, Carlos Alberto Silva [UNESP]; D'Amico-Damião, Victor [UNESP]; Carvalho, Rogério Falleiros [UNESP] (Wiley, 2021)
Photoreceptors are primarily known as key photomorphogenic modulators of various physiological events during plant development. Although there are different groups of photoreceptors, the phytochrome B (phyB) family mediates developmental responses in a wide range of plant species, from seed germination to flowering. In addition, these molecules also regulate abiotic stress acclimation responses, such as salinity, drought, low/high temperature, high light and heavy metals. The signalling pathways mediated by phyB could enhance plant resistance to environmental stresses, as phyB photoreceptors reduce leaf transpiration, increase the antioxidant system, enhance protective pigments and increase the expression of genes related to plant stress acclimation. Thus, the elucidation of positive or negative roles for phyB in these stress tolerance characteristics would provide essential knowledge for genetic engineering, improving plant growth and development in critical environments. In this review, we cover the main findings on how the phyB family works to modulate abiotic stress by discussing biochemical and molecular aspects of the underlying mechanisms operated by these photoreceptors.
Keywords: abiotic stress tolerance; crop breeding; drought; heavy metal; high radiation; phyB; salinity; temperature